Enzymatic Synthesis of 2-Keto-3-Deoxy-6-Phosphogluconate by the 6-Phosphogluconate-Dehydratase From Caulobacter crescentus - Krevet, Sabine; Shen, Lu; Bohnen, Timon; Schoenenberger, Bernhard; Meier, Roland; Obkircher, Markus; Bangert, Klara; Koehling, Rudolf; Allenspach, Eric; Wohlgemuth, Roland; Siebers, Bettina; Bräsen, Christopher (Frontiers in Bioengineering and Biotechnology, 2020)
The availability of metabolic intermediates is a prerequisite in many fields ranging from basic research, to biotechnological and biomedical applications as well as diagnostics. 2-keto-3-deoxy-6-phosphoglucoanate (KDPG) is the key intermediate of the Entner-Doudoroff pathway for sugar degradation and of sugar acid and sugar polymer breakdown in many organisms including human and plant pathogens. However, so far KDPG is hardly available due to missing efficient synthesis routes. We here report the efficient biocatalytic KDPG production through enzymatic dehydration of 6-phosphogluconate (6PG) up to gram scale using the 6-phosphogluconate dehydratase (Entner-Doudoroff dehydratase, EDD) from Caulobacter crescentus (CcEDD). The enzyme was recombinantly produced in Escherichia coli, purified to apparent homogeneity in a simple one-step prodedure using nickel ion affinity chromatography, and characterized with respect to molecular and kinetic properties. The homodimeric CcEDD catalyzed the irreversible 6PG dehydration to KDPG with a Vmax of 61.6 U mg-1 and a KM of 0.3 mM for 6PG. Most importantly, the CcEDD showed sufficient long-term stability and activity to provide the enzyme in amounts and purity required for the efficient downstream synthesis of KDPG. CcEDD completely converted 1 g 6-phosphogluconate (6PG) and a straight forward purification method yielded 0.81 g of stereochemically pure KDPG corresponding to a final yield of 90% as shown by HPLC-MS and NMR analyses.